Facing the challenges of electrodiagnostic studies in the very elderly (>80 years) population. Issue 7 (July 2019) - Punga, Anna Rostedt; Jabre, Joe F.; Amandusson, Åsa
Highlights: Electrodiagnostic findings are presented for 1966 very elderly individuals. EMG normative data from e-norms were similar to those of lab reference values. E-norms provided a wider normality window when applied to nerve conduction data. Abstract: Objective: Studies on electrodiagnostic (EDX) methods usually exclude the very elderly. This also holds true for studies of normal EDX values. We analyzed the outcome and diagnostic value of EDX and collected reference data in a large cohort of patients ≥80 years of age. Methods: Referral information, ICD-10 diagnoses and EDX data were retrieved from all patients ≥80 years of age referred for EDX studies at our department in 1995–2015. Normative data, including reference ranges, were obtained using the extrapolated norms (e-norms) method. Results: 1966 unique patients (2335 examinations) were included. Only 11% were considered to have normal findings. 66% had pathological EDX findings in accordance with the indication for referral. Carpal tunnel syndrome was by far the most common diagnosis. Normative data retrieved using e-norms were similar to those of reference values from healthy subjects regarding EMG multiMUP data, but typically provided a wider normality window when applied to nerve conduction parameters. Conclusions: EDX studies are valuable in the diagnostic work-up of very elderly patients. Using the e-norms method may be a useful alternative when obtaining reference values in this age group. Significance: Our findings provide additional insights to the challenges of evaluating very elderly patients with neuromuscular disease and underline the importance of including this growing part of the patient population in EDX research.